A full air cooling and heating system based on mine water source. (25th December 2018) - Feng, Xiao-Ping; Jia, Zhemin; Liang, Hao; Wang, Zhenping; Wang, Baoqi; Jiang, Xiyin; Cao, Huaixuan; Sun, Xuefeng
Highlights: A new cooling and heating system is designed and has been put into use in mines. The system combines cooling and heating functions based on mine water waste heat. The calculation of cooling and heating loads for the system are illustrated. The unpowered air heat exchanger is developed to meet anti-explosion requirement. The sealing and automatic control technology for pithead are discussed. Abstract: Heat hazard in mine is a problem to be solved urgently because it seriously affects the normal production of mine and the health of workers. This paper puts forward a new method to control seasonal heat hazard of mine by full air cooling system. The system can not only lower temperature and improve environment of mine, but also realize heat supply to meet the antifreezing, bathing requirements for mine and heating requirements for ground buildings. In this paper, taking Jisan coal mine as an example, we introduce the calculation of cooling load and heating load, technical solution, equipment selection, pithead sealing and automatic control technology of full air cooling system. The results show that in summer, after running of the system, inlet air temperature of working face is below 26 °C with the average decrease of 3–5 °C and relative humidity is 80% with the decrease of 10–15%. In winter, inlet air temperature is 12 °C which meets the antifreezing requirements for shaft. At present, cooling system has been put into use in Zhaolou coal mine in Yankuang Group, Jier coal mine, Jisan coal mine and Dongtan coal mine. The operation of the system has played an important role in improving working environment of mine and improving labor productivity.